MENELAAH RITUAL WOLEKA SEBAGAI UPACARA SYUKUR PANEN DAN DAMPAKNYA BAGI HIDUP IMAN UMAT DALAM SUKU BONDOKANIKI PAROKI SANTO MIKAEL ELOPADA - Ngongo, Maria H. Lidya; Oetpah, Dorince (STIPAS Keuskupan Agung Kupang, 2022)
The Woleka ritual is a tradition practiced by the Bondokaniki tribe as a ceremony of thanksgiving for the blessings received. In this research, the researcher examines in more depth the impact of the Woleka ritual ceremony on the life of faith of the people at St. Mikhael Elopada Parish because many problems occur as a result of the implementation of the Woleka ritual ceremony, where there is a waste of property, time and energy as well as a lack of involvement of the people in life. church. The research method used in this research is a qualitative method, in which the author went directly to the field and conducted direct interviews with 7 traditional elders as the main informants and 4 community members as additional informants. From the results of the research, it was found that the people of the Bondokaniki tribe, Saint Mikhael Elopada Parish, have not completely given up their belief in marapu which they consider to be the giver of good fortune. The Woleka ritual held in this parish has both positive and negative impacts on the faith life of the people. The positive impact is that there is constructive togetherness when the people carry out the ceremony and the negative impact is the waste of property, energy and time, and more than that the author finds that the people still live in a dualism of faith.